Islamic environmental thought: an overview on recent developments - Husaini, S. Waqar Ahmed (Internationales Asien-Forum, 1985)
This paper outlines the "revitalisation" of Islam taking the subject of environment as an example. The author first sketches the theological basis of ecological principles in Islam and goes on to describe their historical loss of importance and their "re-activation" as a consequence of several Islamic conferences, within the framework of economic strategies and ecological education programmes. In conclusion the author suggests developing the environmental sciences in Islamic countries.